2010
DOI: 10.1016/j.tripleo.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Notch4 overexpression in ameloblastoma correlates with the solid/multicystic phenotype

Abstract: Present findings suggest that Notch signaling molecules may play differing roles in the acquisition of different ameloblastoma phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…This study also revealed that the expression patterns of Notch receptors and their ligands in the CEOT are distinctive from other odontogenic epithelial neoplasm such as the ameloblastoma 25,26) .…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…This study also revealed that the expression patterns of Notch receptors and their ligands in the CEOT are distinctive from other odontogenic epithelial neoplasm such as the ameloblastoma 25,26) .…”
Section: Discussionmentioning
confidence: 59%
“…Human malignancies demonstrating Notch participation include cancers of the breast 12) , pancreas 13) , ovanes 14) tongue 15) , bone 28) and cartilage 29) . Recently, aberrant Notch signaling has also been implicated in the tumorigenesis of some jaw neoplasms in particular odontogenic neoplasms such as ameloblastoma 22,23,25,26) , ameloblastic fibroma 22) , squamous odontogenic tumor 24) and cemento-ossifying fibroma 35) . However its role in CEOT remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, some papers have published examination results of immunohistochemical expression of Notch and the related singals in some odontogenic neoplasms, including ameloblastoma 2,17) , desmoplastic ameloblastoma 3,26) , ameloblastic carcinoma 5,18) , and squamous odontogenic tumor 4) . These results suggest that Notch Figure 6.…”
Section: Discussionmentioning
confidence: 99%